Hacia la transformación de la cultura organizacional de una agencia pública: Un modelo híbrido de intervención - Ortiz-Torres, Blanca; Santiago-López, Wilmarie; Cruz-Miranda, Liz M.; Núñez-Maldonado, Yamilé; Acosta Ramírez, Tamara Z. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2019)
Towards the transformation of the organizational culture of a public agency: A hybrid intervention model One of the intervention levels of Community Psychology (PC) is the organizational level. The intervention described is syntonic with the values ​​and principles of the PC. The objectives of the project are: assess the elements of the organizational culture of a government agency in Puerto Rico that constitute strengths and weaknesses for the achievement of its mission and develop specific collective actions to motivate and enhance the capacities of all sectors of the organization to get involved in processes of change that increase the efficiency and effectiveness of the agency, as well as the individual and collective satisfaction of employees at all levels. The project was developed in two phases: one for research and one for intervention. All sectors of the organization participated in the design and offered suggestions on its scope and implementation. The intervention phase follows a Competency Model that allows describing the necessary knowledge, skills and behavior for effective performance in an organization. We developed five training modules and pre and post tests were administered before and after the implementation of the training modules. The intervention confirmed the possibility of organizational change with implications for individual change.